Remote mentoring in laparotomic and laparoscopic cancer surgery during Covid-19 pandemic: an experimental setup based on mixed reality. Issue 1 (1st January 2021) - Simone, Michele; Galati, Rocco; Barile, Graziana; Grasso, Emanuele; De Luca, Raffaele; Cartanese, Carmine; Lomonaco, Rocco; Ruggieri, Eustachio; Albano, Anna; Rucci, Antonello; Grassi, Giuseppe
ABSTRACT: In this paper, Mixed Reality (MR) has been exploited in the operating rooms to perform laparoscopic and open surgery with the aim of providing remote mentoring to the medical doctors under training during the Covid-19 pandemic. The employed architecture, which has put together MR smartglasses, a Digital Imaging Player, and a Mixed Reality Toolkit, has been used for cancer surgery at the IRCCS Hospital 'Giovanni Paolo II' in southern Italy. The feasibility of using the conceived platform for real-time remote mentoring has been assessed on the basis of surveys distributed to the trainees after each surgery.